Protective effects of Ginkgo biloba against acetaminophen-induced toxicity in mice - ERCAN, FERİHA; ŞENER, GÖKSEL; YÜKSEL, MERAL (SPRINGER, 2006)
Background: The analgesic acetaminophen (AAP) causes a potentially fatal, hepatic centrilobular necrosis when taken in overdose. It was reported that these toxic effects of AAP are due to oxidative reactions that take place during its metabolism. Objective: In this study, we aimed to investigate the possible beneficial effect of Ginkgo biloba (EGb), an antioxidant agent, against AAP toxicity in mice. Methods: Balb/c mice were injected i.p. with: (1) vehicle, control (C) group; (2) a single dose of 50 mg/kg Ginkgo biloba extract, EGb group; (3) a single dose of 900 mg/kg i.p. acetaminophen, AAP group, and (4) EGb, in a dose of 50 mg/kg after AAP injection, AAP + EGb group. Serum ALT, AST, and tumor necrosis factor-alpha (TNF-alpha) levels in blood and glutathione (GSH), malondialdehyde (MDA) levels, myeloperoxidase (MPO) activity, and collagen contents in liver tissues were measured. Formation of reactive oxygen species in hepatic tissue samples was monitored by using chemiluminescence (CL) technique with luminol and lusigenin probe. Tissues were also examined microscopically. Results: ALT, AST levels, and TNF-alpha were increased significantly (p < 0.001) after AAP treatment, and reduced with EGb. Acetaminophen caused a significant (p < 0.05-0.001) decrease in GSH levels while MDA levels and MPO activity were increased (p < 0.001) in liver tissues. These changes were reversed by EGb treatment. Furthermore, luminol and lusigenin CL levels in the AAP group increased dramatically compared to control and reduced by EGb treatment (p < 0.01). Conclusion: Our results implicate that AAP causes oxidative damage in hepatic tissues and Ginkgo biloba extract, by its antioxidant effects protects the tissues. Therefore, its therapeutic role as a tissue injury-limiting agent must be further elucidated in drug-induced oxidative damage.
Keywords: acetaminophen; Ginkgo biloba; glutathione lipid peroxidation; EXTRACT EGB 761; FREE-RADICALS; IN-VIVO; LIPID-PEROXIDATION; OXIDATIVE STRESS; NITRIC-OXIDE; GLUTATHIONE; HEPATOTOXICITY; RAT; MECHANISMS